Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/1365-2435.12605
|View full text |Cite
|
Sign up to set email alerts
|

The importance of biotic interactions for the prediction of macroinvertebrate communities under multiple stressors

Abstract: Summary1. The community assembly of macroinvertebrates in streams depends on the regional taxon pool, dispersal limitations, local habitat conditions and biotic interactions. By integrating existing knowledge about these processes from theoretical ecology in a mechanistic model, we can test our mechanistic understanding and disentangle multiple stressor effects on community assembly. 2. To assess to which degree we can predict the community composition of macroinvertebrates, we integrated these processes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 29 publications
(43 reference statements)
0
33
0
1
Order By: Relevance
“…Examples for surface water are modelling of discharges from a wastewater treatment plant, industries, and storm water; agricultural/urban runoff; and a food chain [131]. Paillex et al [132] and Schuwirth et al [49] showed the use of such mechanistic models in ecological water quality studies. Mechanistic models allowed them to understand the mechanism behind the presence of taxa based on a combination of traits and environmental conditions [49,132].…”
Section: Recommendation For Statistical Analysis and Model Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples for surface water are modelling of discharges from a wastewater treatment plant, industries, and storm water; agricultural/urban runoff; and a food chain [131]. Paillex et al [132] and Schuwirth et al [49] showed the use of such mechanistic models in ecological water quality studies. Mechanistic models allowed them to understand the mechanism behind the presence of taxa based on a combination of traits and environmental conditions [49,132].…”
Section: Recommendation For Statistical Analysis and Model Selectionmentioning
confidence: 99%
“…Paillex et al [132] and Schuwirth et al [49] showed the use of such mechanistic models in ecological water quality studies. Mechanistic models allowed them to understand the mechanism behind the presence of taxa based on a combination of traits and environmental conditions [49,132]. Nevertheless, these mechanistic models have disadvantages.…”
Section: Recommendation For Statistical Analysis and Model Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, such interactions can be more important than abiotic habitat requirements when predicting community assemblies6, highlighting the importance of integrating interactions in ecological prediction models. Environmental factors may also interact with the genotype of individuals and the genetic constitution of populations.…”
mentioning
confidence: 99%
“…This may result in underestimating the effect of multiple environmental factors on population persistency and the stability of communities4, a risk exemplified by the combination of thermal extremes and drought stress resulting from climate change10. The predictability and generalizability of responses to multiple environmental factors should be incorporated in general global climate change models11, and in ecological risk assessments212 for increased accuracy and prediction power of community assembly modelling6.…”
mentioning
confidence: 99%